Intervention with substance‐abusing mothers: Are there rural–urban differences?. (March 2015) - Shaw, Michele R.; Grant, Therese; Barbosa‐Leiker, Celestina; Fleming, Susan E.; Henley, Sandy; Graham, J. Christopher
<x xml:space="preserve">Abstract</x> Objective The purpose of this study was to examine rural–urban differences among substance‐abusing mothers enrolled in the Parent–Child Assistance Program (PCAP) from 1998 to 2008 in Washington State. Methods This was a longitudinal study utilizing PCAP data reports of 773 women enrolled from 1998 to 2008. Differences across urban–rural PCAP participants were examined. Results Rural participants were more likely to report alcohol use and binge drinking at program intake and at the 3‐year program exit. In addition, throughout the program, rural women were less likely to complete outpatient substance abuse treatment compared to urban participants. Rural women also used less services during the last year including alcohol/drug support and mental health provider services. Findings are troubling when we consider that at program exit, rural participants also reported higher use of alcohol and more suicidal thoughts than those residing in urban areas. Conclusions and Scientific Significance Data presented indicate there are important differences between urban and rural residing participants. Findings highlight the importance of considering the barriers that rural or remote locations might create. Identifying community‐specific needs of substance abusing pregnant or parenting women in both rural and urban settings is crucial for the successful development and improvement of treatment and intervention programs for this vulnerable population of women. (Am J Addict 2015;24:144–152)